CT and MR Imaging Characteristics of Intravestibular Lipoma - Dahlen, Richard T. (AJNR Am J Neuroradiol, 2002)
BACKGROUND AND PURPOSE: Intracranial lipomas are uncommon congenital malformations that most often are asymptomatic. A rare subset of intracranial lipomas arises within the vestibule of the inner ear, which can cause sensorineural hearing loss. We present the CT and MR imaging characteristics of lipomas within the vestibule of the inner ear and propose a pathogenetic mechanism for this malformation. METHODS: We retrospectively reviewed five cases of vestibular lipoma. T1-weighted axial conventional spin-echo and T2-weighted axial fast spin-echo sequences were performed in all five cases. Four patients underwent T1-weighted fat-saturated imaging, and one underwent CT scanning with Hounsfield units measured. RESULTS: Four female patients ranging in age from 10 to 40 years and one 26-year-old male patient had sensorineural hearing loss. Two patients had progressive high-frequency loss; one, sudden-onset high-frequency loss; and two, congenital high-frequency loss. All had lesions within the vestibule that displayed hyperintensity on T1-weighted images, isointensity to slight hypointensity on T2-weighted fast spin-echo images, hypointensity with fat saturation, and fat attenuation on CT scans. Three of the cases were associated with lipoma of the cerebellopontine angle. In none of these cases were the cerebellopontine angle and labyrinthine lipomas contiguous. CONCLUSION: Intravestibular lipoma is considered when a focal hyperintense lesion is identified within the vestibule of the inner ear on T1-weighted MR images. Lesion hypointensity on fat-saturated T1-weighted MR images verifies its lipomatous nature and separates it from intralabyrinthine hemorrhage or highly proteinaceous fluid.